Food Security Innovation In Halal Certification Regulation On Food Products (Between Lppom MUI And BPJPH Ministry Of Religion) - Gunawati, Anne; Agus, Dede; Muslih, Muhamad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
The issue in this study is that regulations on halal certification have a very large role in supporting the national food security program. Halal certification on products is very important for consumers because in some cases people are reluctant to buy food products that do not have a halal label on their packaging. The government ratified Law Number 33 of 2014 concerning Halal Product Guarantee (UU JPH) which after being investigated it turned out that the JPH Law did not strengthen the existence of LPPOM MUI, but gave authority to the Government or the Ministry of Religion to form a new institution other than LPPOM MUI, namely the Product Assurance Organizing Body. Halal (BPJPH). The research objective to be achieved from this research is to ensure that BPJPH can cooperate with MUI in terms of halal auditor certification and the determination of halal products in order to support national food security. This study uses a normative juridical legal research method, this research is descriptive analytical and uses primary data sources and secondary data sources. The key finding of this research is that the authority of the MUI remains important because MUI is the institution authorized to issue a fatwa on the determination of the halalness of a product which is then submitted to BPJPH as the basis for issuing a halal certificate. The importance of this research to be discussed because with the union of the two institutions, hopefully in the future Indonesia will become the center of world halal products with various products made in Indonesia so that national food security will be maintained.